Cognitive home environment of infants, toddlers and preschoolers: A study from a hospital setting - Canaloglu, Sinem Kortay; Dogan, Derya Gumus; Buyukavci, Mehmet Akif; Arslan, Feyzullah Necati (Annals of Medical Research, 2021)
Aim: The purpose of this study was to determine the Cognitive Home Environment (CHE) of young children who apply to the hospital for various reasons.Material and Methods: In total 121 mothers participated. CHE was measured by The StimQ – (Infant, Toddler and Preschool) Home Environment Assessment Tools and sociodemographic characteristics of the families were noted.Results: Averages of total StimQ scores were lowest in Infant Group (IG) with 13.7 points out of 43; 15.9 points out of 39 in Toddler Group (TG); 27.78 points out of 49 in Preschool Group (PG). There was a significant difference in the Total StimQ scores of mothers with high level of education in Toddler (p=.005) and Preschool (p=.000) groups. Looking at childrens' books increased with age. Only 15% of the mothers in the IG, 32.5% in the TG, and 90% in the PG were looking at children's books with their children.Conclusion: The CHE of young children is not enough to serve for optimal development, especially the infants. High maternal education iseffects CHE positively. Applying STIMQ can be a good opportunity to explore CHE of children in hospital settings.
Keywords: Cognitive home environment; early childhood; StimQ